PERKEMBANGAN AJARAN BUDDHA DALAM TRILOGI PEMBEBASAN - I Komang Suastika Arimbawa; G. Arya Anggriawan (Sanjiwani: Jurnal Filsafat, 2020)
Before the birth of Buddhism, Indian society was familiar with various beliefs, ranging from those of austerities, religious ceremonies, Upanisad, materialists (having fun), and Jainism. The Buddha taught that the ultimate goal of human life is nirvana, which is not a gift from God or the gods, but can only be obtained by one's own efforts. Buddhist philosophy was born from the teachings of the Buddha Gautama obtained from the results of his enlightenment, called Catvari Ārya-satyani. These four main truths have serious philosophical implications, because some of the doctrines are born from these truths, namely: the doctrine of karma, the doctrine of impermanence (anityavāda), the doctrine of the non-existence of the spirit, the doctrine of no God, the doctrine of relative existence, and the doctrine of the law of causation consequence. The path that can lead to the elimination of suffering is called the Aṣṭāṅgika-mārga. These eight stairs are able to get rid of ignorance and desire, illuminate the mind and cause perfect balance and calm. The Buddha first taught the Dhamma to five ascetics in the Isipatana deer park, Sarnath. He guided them to the Arahat. To preserve and convey Buddhist teachings to the wider community, a Buddhist council was held six times. Then, relating to religious matters, Buddhism was divided into two major schools, namely Hinayāna and Mahāyāna. Ethics or morality in Buddhism can be found in three sentences, such as avoiding bad deeds, adding to good deeds, and cleansing the heart, all of which are summarized in Buddhist Pancasila and Pancadhamma. The main teachings of the Buddha are recorded in three sacred books called Tripitaka. Between philosophy, religion and ethics in Buddhism has a very close relationship in its goal of achieving liberation, because Buddhism does not separate knowledge from behavior, theory and practice.